EFFECT OF LOW-TEMPERATURE CARBURIZATION TREATMENT ON THE HARDNESS BEHAVIOR OF Alsl316 AUSTENITIC STAINLESS STEEL - Bello, Kamilu Adeyemi; Abubakar, Ibrahim I.; Bello, Lateef O.; Dodo, Rayyan M.; Musa, Zahradeen; Bala, Muhammad Nura; Hayatu, M. A. (FUDMA Journal of Sciences, 2025)
There has been significant progress in the surface modification of stainless steel in order to enhance its surface hardness without major loss in other important properties. In this work, the possibility of enhancing the hardness property of austenitic stainless steel through a low-temperature pack carburization process was explored and investigated. Taguchi approach with L9 orthogonal array was used to optimize the hardness property of the carburized steel via the manipulation of the process parameters viz: carburizing temperature (350, 450, 550 oC), carburizing time (8,16, 24hrs) and carburizer/energizer ratio (90:10, 80:20,70:30). The surface hardness profiles of the carburized layer were investigated. Taguchi analysis result shows that optimal hardness of 407Hv was achieved. The optimization of the carburized surface properties revealed that the carburizing temperature of 550 oC, carburizing time of 24hrs and carburizer/energizer ratio of 90:10 are the prominent factors and levels for achieving optimal condition respectively.  The models for optimal conditions were validated and the prediction adequacy are found to be within the limit of 2-6% prediction error, indicating the models are accurate and adequate to predict the responses. Optical microscope micrographs and morphologies indicates that the modified steel layer obtained at the optimal condition shows mild deeper case profile compared to non-treated stainless-steel samples. Equivalent of 104% improvement in the case hardness was achieved for the samples investigated with optimized condition. The level of improvement attained in the hardness therefore suggest that the ultimate objective of surface modification of austenitic stainless steel investigated in this study has been achieved.
Keywords: Carburizer; Energizer; Hardness; Low-Temperature; Treatment